2013
DOI: 10.1021/la402910a
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diffraction and Density Functional Theory Calculations of Halogen-Bonded Cocrystal Monolayers

Abstract: This work describes the combined use of synchrotron X-ray diffraction and density functional theory (DFT) calculations to understand the cocrystal formation or phase separation in 2D monolayers capable of halogen bonding. The solid monolayer structure of 1,4-diiodobenzene (DIB) has been determined by X-ray synchrotron diffraction. The mixing behavior of DIB with 4,4′-bipyridyl (BPY) has also been studied and interestingly is found to phase-separate rather than form a cocrystal, as observed in the bulk. DFT cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 40 publications
5
37
0
Order By: Relevance
“…31 In this co-layer, the molecules form extended linear chains of alternating DITFB and BPY, with evidence of halogen bond formation between the iodine atoms of DITFB and the nitrogen atoms of BPY, as deduced by the short internuclear separation; this is further supported by recent simulation work. 32 This structure is in good agreement with the bulk behaviour, where halogen bond formation is also observed. 33 Interestingly, we have recently demonstrated that 1,4-diiodobenzene (DIB - Fig.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…31 In this co-layer, the molecules form extended linear chains of alternating DITFB and BPY, with evidence of halogen bond formation between the iodine atoms of DITFB and the nitrogen atoms of BPY, as deduced by the short internuclear separation; this is further supported by recent simulation work. 32 This structure is in good agreement with the bulk behaviour, where halogen bond formation is also observed. 33 Interestingly, we have recently demonstrated that 1,4-diiodobenzene (DIB - Fig.…”
Section: Introductionsupporting
confidence: 84%
“…1c), the non-fluorinated analogue of DITFB, does not form a halogen bonded co-layer with BPY when physisorbed on graphite. 32 This contrasts with the bulk behaviour, where a BPY-DIB co-crystal is observed. 33 The lack of halogen bond formation in the mixed overlayer of DIB-BPY has been attributed to the weaker halogen bonds formed by DIB compared to DITFB, relative to the energies of the two separate materials, a conclusion supported by DFT calculations.…”
Section: Introductionmentioning
confidence: 90%
“…48,49 As mentioned in the Method section, we use a Cu{110}-(3 Â 2) cell for all the calculations regarding pure gly and gly/H 2 O co-adsorption, and a smaller c(2 Â 2) cell to calculate the adsorption energy and surface energy for the water monomer and for the saturated (intact and half dissociated) water monolayer on Cu{110}. This method has been recently tested for addressing the relative intensity of hydrogen and halogen bonding compared to long-range van der Waals (vdW) interactions in phenazine overlayers and halogen-bonded supramolecular networks on graphite where it appears to perform very well.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, a complete vibrational study of NF-DMAP salt and NF by Raman and infrared (IR) spectral analysis combined with density functional theory (DFT) approach has been performed. It should be mentioned that vibrational spectroscopy is the most accepted analytical tool, and DFT is the utmost acknowledged theoretical approach to study the molecular structure of different molecular systems [19][20][21][22][23][24]. In order to attain a comprehensive analysis of the hydrogen bond patterns, both DFT and spectroscopic methods have been used.…”
Section: Introductionmentioning
confidence: 99%